A probable role of blood lead levels on some haematological parameters in traffic police, Lahore, Pakistan. (May 2016) - Khan, Shafaat Yar; Arshad, Muhammad; Arshad, Najma; Shafaat, Shazia; Tahir, Hafiz Muhammad
The impact of elevated blood lead level on some haematological parameters was studied in the field force of Lahore traffic police, in Pakistan. The blood samples were tested for total leucocytes count (TLC) and differential leucocytes count in the persons with high and low blood lead levels. The TLC and percentage of neutrophils and eosinophils were observed as being significantly elevated in the policemen. No significant change was observed in the percentage of lymphocytes, while the percentage of monocytes was observed as being significantly less in the field force of traffic police.